The effect of the penalty system on market prices in the Korea ETS - Weonseek Kim; Jongmin Yu (Carbon Management, 2018)
This study analyzes the effect of the penalty system in an emission trading scheme (ETS) on pricing and abatement activities. No previous studies have shown that the ways of penalizing for unretired permits specifically might have a crucial role in permit pricing. Most studies show that the penalty rate is fixed, as in the EU-ETS, but this paper focuses on the mechanism that price affects penalty and this again affects price. The Korea ETS case is examined as an example in which the per-unit penalty for unretired permits is determined by the average market price. Based on simple analytical modeling, this study derives policy implications that differ from the pre-determined penalty rate system: that the penalty system linked with market prices causes downward pressure on market prices, that the maximum rate is not very meaningful in pricing, that the multiplication level of the penalty rate affects market prices, and that this price-linked penalizing system can affect the overall level of abatement.